Análise da atividade antiviral in vitro de compostos fenólicos como potencial alternativa para o controle do SARS-CoV-2 - Brisighello, Camila Sillos Rosas (2024)
The health emergency generated by the COVID-19 pandemic in recent years has instigated the search for scientific strategies to mitigate the damage caused by the virus to humans. Even with FDA-approved drugs, there are still restrictions on their use in patients and some are only available for hospital use. In addition, the higher cost of these drugs can pose a challenge to widespread accessibility. Brazilian biodiversity is a promising source for prospecting molecules with therapeutic potential. This opens up a horizon of opportunities for the discovery and development of new strategies for controlling SARS-CoV-2. This work aimed to investigate the antiviral activity of phenolic compounds from Brazilian biodiversity and their interaction with specific protein targets of SARS-CoV-2. Thus, molecules obtained from compounds present in the extract library of Embrapa Agroindústria Tropical (Tropical DB) were evaluated for cell viability and antiviral activity. In the first screening, Vero cells were used using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) reduction method. The concentrations obtained which maintained viability above 70% in the MTT test were used in the viral neutralization tests (PRNT). Based on the PRNT results, in silico molecular docking tests were carried out for the selected molecules against three targets: Spike protein, Mpro protease and RNA-Dependent RNA-Polymerase (RdRp). The three compounds selected in the screening were: chlorogenic acid, ellagic acid and thymol, with concentrations that reduce cell viability and metabolic status by up to 30% of: 100 μg/mL; 3.125 μg/mL and 25 μg/mL, respectively. The results of the PRNT test, when the molecules were directly in contact with the virus, showed a percentage of viral plaque formation of 96.7%, 30.9% and 89.1% for chlorogenic acid, ellagic acid and thymol, respectively. Ellagic acid stood out for its 69.1% viral inhibition. None of the phenolic compounds analyzed showed viral activity when they were analyzed if they acted alone on the cells. The IC50 of ellagic acid was 0.3492 µg/mL. In molecular docking, chlorogenic acid had the best energy performance when evaluated for protein S, ellagic acid had the highest score for RdRp and thymol had a triple mode of action. This highlights the potential, especially of ellagic acid, as a possible candidate molecule for future studies aimed at developing treatment alternatives for COVID-19. This molecule can be used in human supplementation, benefiting individuals at high risk of serious complications from COVID-19 and benefiting countries with financial and health infrastructure restrictions. These findings emphasize the importance of research that seeks to establish new alternatives in the discovery of antiviral agents, contributing to the understanding of the importance of the evolution of products derived from natural compounds.